2015
DOI: 10.1039/c5ta02193f
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical insight into the roles of cocatalysts in the Ni–NiO/β-Ga2O3photocatalyst for overall water splitting

Abstract: Nin and (NiO)n clusters located on different β-Ga2O3(100) surface sites participate in photocatalytic proton reduction and water oxidation reactions, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 63 publications
2
32
0
Order By: Relevance
“…Ju et al. showed that although PBE significantly underestimates the bandgap of the Ga 2 O 3 , it predicts identical density of states and line shapes to that calculated by using the HSE06 hybrid functional, which can predict the exact bandgap . Angle‐resolved photoemission spectroscopy and DFT studies agree that β‐Ga 2 O 3 is an indirect material with the CBM at Gamma and VBM at M(1/2 1/2 1/2 ) .…”
Section: Resultsmentioning
confidence: 94%
“…Ju et al. showed that although PBE significantly underestimates the bandgap of the Ga 2 O 3 , it predicts identical density of states and line shapes to that calculated by using the HSE06 hybrid functional, which can predict the exact bandgap . Angle‐resolved photoemission spectroscopy and DFT studies agree that β‐Ga 2 O 3 is an indirect material with the CBM at Gamma and VBM at M(1/2 1/2 1/2 ) .…”
Section: Resultsmentioning
confidence: 94%
“…23 The most stable low index surface of b-Ga 2 O 3 is the (100)-B type, as has been proven by theoretical calculations and experiments. 20,24 The absorption behaviors of materials such as CO 2 , 25 CH 4 , 26 H 2 , [27][28][29] formate, 2 and CH 3 OH, 30 on Ga 2 O 3 have been investigated using DFT methods, with most of these simulations based on the (100) termination surface. However, the large bandgap of b-Ga 2 O 3 (about 4.8 eV) leads to a low utilization of the solar spectrum because the material is only active in the ultraviolet region.…”
Section: Introductionmentioning
confidence: 99%
“…These values are almost the same as previously reported calculation results and in good agreement with the experimental result. 17 , 21…”
Section: Results and Discussionmentioning
confidence: 99%